Returning Fire to the Land: Celebrating Traditional Knowledge and Fire - Lake, Frank K.; Wright, Vita; Morgan, Penelope; McFadzen, Mary; McWethy, Dave; Stevens-Rumann, Camille (Journal of forestry, 2017)
North American tribes have traditional knowledge about fire effects on ecosystems, habitats, and resources. For millennia, tribes have used fire to promote valued resources. Sharing our collective understanding of fire, derived from traditional and western knowledge systems, can benefit landscapes and people. We organized two workshops to investigate how traditional and western knowledge can be used to enhance wildland fire and fuels management and research. We engaged tribal members, managers, and researchers to formulate solutions regarding the main topics identified as important to tribal and other land managers: cross-jurisdictional work, fuels reduction strategies, and wildland fire management and research involving traditional knowledge. A key conclusion from the workshops is that successful management of wildland fire and fuels requires collaborative partnerships that share traditional and western fire knowledge through culturally sensitive consultation, coordination, and communication for building trust. We present a framework for developing these partnerships based on workshop discussions.